Ajuste econômico e desemprego recente no Brasil metropolitano - POCHMANN, MARCIO (Estudos Avançados, 2015)
In three consecutive, concatenated parts, this paper examines the evolution of unemployment rates in early 2015, premising that changes in the labor market, signaled mainly by rising unemployment, are fundamentally generated by the growing recession of the Brazilian economy. The first part outlines the main changes in income and employment in the labor markets of metropolitan areas from January to July 2015. The second part briefly describes the most important features arising from the recent increase in unemployment rates. Finally, the third part records and compares the effects of economic adjustment policies on unemployment over selected years of the past three decades, making it possible to assess how intensely the current unemployment rate has evolved vis-à-vis other historical moments.